Advanced applications of computational mathematics - Kumar, Akshay; Ram, Mangey; Srivastava, H. M. (River Publishers series in mathematical and engineering sciences., 2021)
This book "Advanced Applications of Computational Mathematics" covers multidisciplinary studies containing advanced research in the field of computational and applied mathematics. The book includes research methodology, techniques, applications, and algorithms. The book will be very useful to advanced students, researchers and practitioners who are involved in the areas of computational and applied mathematics and engineering.